Cytokine and epigenetic regulation of programmed death‐ligand 1 in stem cell differentiation and cancer cell plasticity. (28th June 2021) - Kuo, Ming‐Han; Chen, Pei‐Yu; Yang, Yi‐Ping; Zheng, Ming‐Yi; Miao, Chia‐Cheng; Wen, Kuo‐Chang; Chang, Kuo‐Ming; Chou, Shih‐Jie; Wang, Mong‐Lien; Chiou, Shih‐Hwa; Chou, Yu‐Ting
Abstract: Programmed death‐ligand 1 (PD‐L1), an immune checkpoint ligand, is recognized as a potential target for cancer immunotherapy as well as for the induction of transplantation tolerance. However, how the crosstalk between stem cell programming and cytokine signaling regulates PD‐L1 expression during stem cell differentiation and cancer cell plasticity remains unclear. Herein, we reported that PD‐L1 expression was regulated by SOX2 during embryonic stem cell (ESC) differentiation and lung cancer cell plasticity. PD‐L1 was induced during ESC differentiation to fibroblasts and was downregulated during SOX2‐mediated reprogramming of fibroblasts to induced pluripotent stem cells (iPSCs). Furthermore, SOX2 activation affected cancer cell plasticity and inhibited PD‐L1 expression in lung cancer cells. We discovered that the H3K27ac signal at the PD‐L1 locus was enhanced during ESC differentiation to fibroblasts as well as during cancer plasticity of SOX2‐positive lung cancer cells to SOX2‐negative counterparts. Romidepsin, an epigenetic modifier, induced PD‐L1 expression in lung cancer cells, whereas TGF‐β stimulation downregulated SOX2 but upregulated PD‐L1 expression in lung cancer cells. Furthermore, in addition to PD‐L1, the expressions of EGFR and its ligand HBEGF were downregulated by activation of endogenous SOX2 expression during lung cancer cell plasticity and iPSC reprogramming, and the activation of EGFR signaling by HBEGF upregulated PD‐L1 expression in lung cancer cells. Together, our results reveal the crosstalk between SOX2 programming and cytokine stimulation influences PD‐L1 expression, and these findings may provide insights into PD‐L1‐mediated therapeutics. Abstract : SOX2‐mediated reprogramming of fibroblasts or cancer plasticity of lung cancer cells inhibits programmed death‐ligand 1 (PD‐L1) expression (upper). SOX2 expression is negatively associated with PD‐L1 as well as HBEGF/EGFR and TGF‐β signaling molecules (middle). SOX2 interacts with HDAC1, which silences PD‐L1 expression (lower left). TGF‐β induces PD‐L1 expression via MEK pathway, while HBEGF/EGFR enhances PD‐L1 expression through MEK and AKT pathways (lower right).